An AC active filter for use at capacitor commutated HVDC converters. - Gole, A.M (IEEE Transactions on power delivery)
This paper discusses the application of an AC side active filter in HVDC schemes involving capacitor commutated converters. A suitable topology and control algorithm is selected to achieve the necessary objective of filtering the lower order characteristic harmonics. The dependence of the filter's rating on parameters such as the extent of de-tuning of its passive elements is investigated. The performance of this filter in a capacitor commutated converter application is evaluated using an electromagnetic transient simulation program